Dysbiosis contributes to fibrogenesis in the course of chronic liver injury in mice. Issue 5 (25th February 2014) - De, Samuele; Rychlicki, Chiara; Agostinelli, Laura; Saccomanno, Stefania; Candelaresi, Cinzia; Trozzi, Luciano; Mingarelli, Eleonora; Facinelli, Bruna; Magi, Gloria; Palmieri, Claudio; Marzioni, Marco; Benedetti, Antonio; et al.
<x xml:space="preserve">Abstract</x> Nonalcoholic fatty liver disease (NAFLD) may lead to hepatic fibrosis. Dietary habits affect gut microbiota composition, whereas endotoxins produced by Gram‐negative bacteria stimulate hepatic fibrogenesis. However, the mechanisms of action and the potential effect of microbiota in the liver are still unknown. Thus, we sought to analyze whether microbiota may interfere with liver fibrogenesis. Mice fed control (CTRL) or high‐fat diet (HFD) were subjected to either bile duct ligation (BDL) or CCl4 treatment. Previously gut‐sterilized mice were subjected to microbiota transplantation by oral gavage of cecum content obtained from donor CTRL‐ or HFD‐treated mice. Fibrosis, intestinal permeability, bacterial translocation, and serum endotoxemia were measured. Inflammasome components were evaluated in gut and liver. Microbiota composition (dysbiosis) was evaluated by Pyrosequencing. Fibrosis degree was increased in HFD+BDL versus CTRL+BDL mice, whereas no differences were observed between CTRL+CCl4 and HFD+CCl4 mice. Culture of mesenteric lymph nodes showed higher density of infection in HFD+BDL mice versus CTRL+BDL mice, suggesting higher bacterial translocation rate. Pyrosequencing revealed an increase in percentage of Gram‐negative versus Gram‐postive bacteria, a reduced ratio between Bacteroidetes and Firmicutes, as well as a dramatic increase of Gram‐negative Proteobacteria in HFD+BDL versus CTRL+BDL mice. Inflammasome expression was increased in liver of fibrotic mice, but significantly reduced in gut. Furthermore, microbiota transplantation revealed more liver damage in chimeric mice fed CTRL diet, but receiving the microbiota of HFD‐treated mice; liver damage was further enhanced by transplantation of selected Gram‐negative bacteria obtained from cecum content of HFD+BDL‐treated mice. Conclusions: Dietary habits, by increasing the percentage of intestinal Gram‐negative endotoxin producers, may accelerate liver fibrogenesis, introducing dysbiosis as a cofactor contributing to chronic liver injury in NAFLD. (Hepatology 2014;59:1738–1749)